2022
DOI: 10.1038/s41477-022-01127-9
|View full text |Cite
|
Sign up to set email alerts
|

Genomes of leafy and leafless Platanthera orchids illuminate the evolution of mycoheterotrophy

Abstract: To improve our understanding of the origin and evolution of mycoheterotrophic plants, we here present the chromosome-scale genome assemblies of two sibling orchid species: partially mycoheterotrophic Platanthera zijinensis and holomycoheterotrophic Platanthera guangdongensis. Comparative analysis shows that mycoheterotrophy is associated with increased substitution rates and gene loss, and the deletion of most photoreceptor genes and auxin transporter genes might be linked to the unique phenotypes of fully myc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 118 publications
(150 reference statements)
0
36
0
Order By: Relevance
“…We suspected that PhSEPs genes may act as the “glue” for MADS-box transcription factor complex formation to regulate perianth formation in P. henryanum . In recent years, the genomes of some orchids including Apostasia shenzhenica , Phalaenopsis aphrodite , Vanilla planifolia , C. goeringii , Dendrobium chrysotoxum , Platanthera zijinensis , and Platanthera guangdongensis were published ( Zhang et al, 2017 , 2021 ; Chao et al, 2018 ; Hasing et al, 2020 ; Sun et al, 2021 ; Li et al, 2022 ). By contrast, the occurrence of whole-genome duplication in Paphiopedilum results in a genome that is very large and complex Besides, A-, B-, C-, D-class MADS-box genes in P. henryanum have not been systematically identified, which restricts the analysis of the protein–protein interaction network.…”
Section: Discussionmentioning
confidence: 99%
“…We suspected that PhSEPs genes may act as the “glue” for MADS-box transcription factor complex formation to regulate perianth formation in P. henryanum . In recent years, the genomes of some orchids including Apostasia shenzhenica , Phalaenopsis aphrodite , Vanilla planifolia , C. goeringii , Dendrobium chrysotoxum , Platanthera zijinensis , and Platanthera guangdongensis were published ( Zhang et al, 2017 , 2021 ; Chao et al, 2018 ; Hasing et al, 2020 ; Sun et al, 2021 ; Li et al, 2022 ). By contrast, the occurrence of whole-genome duplication in Paphiopedilum results in a genome that is very large and complex Besides, A-, B-, C-, D-class MADS-box genes in P. henryanum have not been systematically identified, which restricts the analysis of the protein–protein interaction network.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, orchid distribution is considered associated with OMF diversity [ 75 ], which is jointly regulated by environmental factors, spatiotemporal variations, biogeography, and the phylogenetic constraints of host orchids [ 72 ]. Multifaceted evidence from radiocarbon (∆ 14 C), molecular markers and genomic data suggested that both fully mycoheterotrophic and partial mycoheterotrophic orchids obtain carbon from fungi [ 76 , 77 ]. And the concept that OMF receives nothing in return has been overturned by a study that examined the expression of fungal and plant nitrogen (N) transport and assimilation genes, the results showed mycoheterotrophic orchid and its fungal partner have a mutualistic association [ 78 ].…”
Section: Orchid Conservationmentioning
confidence: 99%
“…Another interesting feature in orchids is that all orchids showed mycorrhizal fungi association (partial mycoheterotrophy) during seed germination and the early stage of protocorms [ 92 ]. Genomes of obligate mycoheterotrophic orchids were reported in two species in Gastrodia [ 93 95 ] and Platanthera guangdongensis [ 77 ]. Both studies revealed contracted plastid genomes and substantial loss of genes involved in photosynthesis of fully mycoheterotrophic orchids, while elevated expression of trehalase could be a critical adaptation for mycoheterotrophy, enabling orchids to hijack trehalose from fungi and resynthesize it as sucrose for internal use [ 77 ].…”
Section: Whole Genome Sequencingmentioning
confidence: 99%
“…zijinensis and Pl. guangdongensis using PacBio technologies [17]. The total length of the genome assembly was 4.19 Gb with a contig N50 value of 1.77 Mb for the Pl.…”
Section: Expanded Database Contentmentioning
confidence: 99%